An application of the student relationship management concept - Piedade, Maria Beatriz (2009)
It is largely accepted that a way to promote the students’ success is by implementing processes that allow the students closely monitoring, the evaluation of their success and the approximation to their day-by-day activities. However, the implementation of these processes does not take place in many Higher Education Institutions due to the lack of appropriates institutional practices and an adequate technological infrastructure able to support these practices. In order to overcome these conceptual and technological limitations, this paper presents the Student Relationship Management System (SRM System). The SRM System supports the SRM concept and the SRM practice, also here presented, and it is implemented using the technological infrastructure that supports the Business Intelligence (BI) systems. The SRM system was used in an application case (in a real context) to obtain knowledge about the students and their academic behaviour. Such information is fundamental to support the decision-making associated with the teachinglearning process. All the obtained results are also presented and analysed in this paper.